Evaluation of Rational Antibiotic Use in Community Acquired Pneumonia Patients at RSUD Dr. Harjono Ponorogo - Iswandi Iswandi; Samuel Budi Harsono; Farda Hakimah (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Pneumonia remains a major health problem in Indonesia, with a national prevalence of 0.48% based on health worker diagnosis. Irrational antibiotic use may increase bacterial resistance, prolong hospitalization, and worsen clinical outcomes. This study aimed to evaluate the rationality of antibiotic use in adult community-acquired pneumonia (CAP) patients at RSUD Dr. Harjono Ponorogo, analyze its association with clinical outcomes, and identify factors contributing to irrational antibiotic use. This analytic observational study employed a retrospective cohort design involving adult CAP inpatients treated from January to December 2023. The rationality of antibiotic therapy was evaluated using the Gyssens method based on the American Thoracic Society/Infectious Diseases Society of America (ATS/IDSA) guidelines and the Indonesian National Guidelines for Medical Services. Data were analyzed descriptively and inferentially using the chi-square test. The results showed that 69% of patients received rational antibiotic therapy, while 31% received irrational therapy. Clinical outcomes were predominantly categorized as improved (74.7%) with an average length of stay of 3 to 5 days. Statistical analysis demonstrated a significant association between rational antibiotic use and favorable clinical outcomes (p=0.028; OR=3.58). Fishbone analysis identified several contributing factors to irrational antibiotic use, including patient-related factors, healthcare providers, drug availability, laboratory support, and managerial aspects. In conclusion, rational antibiotic use was significantly associated with better clinical outcomes in CAP patients. These findings highlight the importance of optimizing antibiotic stewardship programs to improve pneumonia management in regional hospitals.